Cognitive Load Theory and worked examples. (2nd November 2019) - Arora, Kiran
Abstract : Can putting yourselves in your students' shoes help you to become a better teacher? Former maths teacher turned research manager Kiran Arora reflects on his experience of using Cognitive Load Theory and worked examples to tackle new areas of learning